AKSEPTABILITAS TERJEMAHAN DONGENG HAENSEL UND GRETEL - Rosyidah Rosyidah; Deddy Kurniawan; Desti Nur Aini (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2017)
This study was conducted to explore and describe the clarity, the naturalness, the emotional expressions and the styles used in the translation of Hansel and Gretel fairytale. The data were collected through document analysis and analysed by using three main steps, namely data reduction, data display, and data conclusion and verification. The results showed that (1) there are many forms which are not clear and not easy to understand; (2) there are many forms which are correct grammatically but not natural; (3) emotion is expressed through words, phrases and sentences which describe anger, fear, sadness, joy and calmness; and (4) there are five styles used by the translator: simile, hyperbol, assonace, repetition and personification.  Permalink/DOI: dx.doi.org/10.17977/um015v45i12017p064